Annual research review: quality of life and childhood mental and behavioural disorders - a critical review of the research - Jonsson, Ulf; Bölte, Sven (The journal of child psychology and psychiatry, 2017)
Background An individual's subjective perception of well-being is increasingly recognized as an essential complement to clinical symptomatology and functional impairment in children's mental health. Measurement of quality of life (QoL) has the potential to give due weight to the child's perspective. Scope and methodology Our aim was to critically review the current evidence on how childhood mental disorders affect QoL. First, the major challenges in this research field are outlined. Then we present a systematic review of QoL in children and adolescents aged 0-18 years formally diagnosed with a mental and behavioural disorder, as compared to healthy or typically developing children or children with other health conditions. Finally, we discuss limitations of the current evidence base and future directions based on the results of the systematic review and other relevant literature. Findings and conclusions The systematic review identified 41 eligible studies. All were published after the year 2000 and 21 originated in Europe. The majority examined QoL in neurodevelopmental disorders, including attention-deficit hyperactivity disorder (k = 17), autism spectrum disorder (k = 6), motor disorders (k = 5) and intellectual disability (k = 4). Despite substantial heterogeneity, studies demonstrate that self-reported global QoL is significantly reduced compared to typical/healthy controls across several disorders and QoL dimensions. Parents’ ratings were on average substantially lower, casting doubt on the validity of proxy-report. Studies for large diagnostic groups such as depressive disorders, anxiety disorders, (early onset) schizophrenia and eating disorders are largely lacking. We conclude that representative, well-characterized normative and clinical samples as well as longitudinal and qualitative designs are needed to further clarify the construct of QoL, to derive measures of high ecological validity, and to examine how QoL fluctuates over time and is attributable to specific conditions or contextual factors.